An assessment of techniques suitable for the diagnosis of sickle-cell disease and haemoglobin C disease in cord blood samples. Issue 6 (September 1970) - Yawson, G. I.; Huntsman, R. G.; Metters, J. S.
Abstract : Agar gel, cellulose acetate, and starch gel electrophoresis are all capable of diagnosing sickle-cell anaemia, sickle-cell haemoglobin C disease, and haemoglobin C disease in cord blood samples. Of these three electrophoretic techniques, agar gel is the easiest to interpret. Paper electrophoresis can reliably and rapidly detect sickle haemoglobin and haemoglobin C in cord blood samples. Being incapable of differentiating foetal and normal adult haemoglobin, the value of paper electrophoresis is limited to an initial screening procedure.